1983
DOI: 10.1002/1097-0142(19830501)51:9<1621::aid-cncr2820510912>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Cytochemical and competitive protein binding assays for estrogen receptor in breast disease a comparative study of 62 cases

Abstract: Estrogen receptor content of breast lesions was estimated using a fluorescent cytochemical technique and a competitive protein binding assay. Of 48 cancers examined, an equal proportion contained significant quantities of receptor by either method (62.5%). The concordance between methods for individual patients was also 62.5%. A greater proportion (26%) of patients younger than 45 years of age had receptor‐positive cancers using the cytochemical method than were found by the biochemical method (10%). Benign br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1985
1985
1992
1992

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…Reasons for differences in the results of estrogen‐and progesterone‐receptor studies in primary cutaneous melanoma may be due to variation in correlation between the assays used, possible nonspecific binding of the hormone used in the assays, or chance variation due to small patient populations. Although some authors report good correlation between the fluorescent techniques compared with the standard dextran charcoal and sucrose density gradient assays in breast carcinoma, 12, 16, 17 with apparent specificity for estrogen and progesterone binding, 10, 11, 17 others report poor correlation 18–21 . No comparative studies were found on review of published reports in melanoma studies.…”
Section: Commentsmentioning
confidence: 99%
“…Reasons for differences in the results of estrogen‐and progesterone‐receptor studies in primary cutaneous melanoma may be due to variation in correlation between the assays used, possible nonspecific binding of the hormone used in the assays, or chance variation due to small patient populations. Although some authors report good correlation between the fluorescent techniques compared with the standard dextran charcoal and sucrose density gradient assays in breast carcinoma, 12, 16, 17 with apparent specificity for estrogen and progesterone binding, 10, 11, 17 others report poor correlation 18–21 . No comparative studies were found on review of published reports in melanoma studies.…”
Section: Commentsmentioning
confidence: 99%
“…Τα ποσοστά αυτά εάν εξαιρέσουμε τις οριακές περιπτώσεις ανεβαίνουν σε 65% και 77,3% αντίστοιχα. Ο Jacobs 60 είχε συμφωνία 62,5% μεταξύ των δυο μεθόδων και θεω ρεί, ότι η μέθοδος του ανοσοφθορισμού αξίζει περαιτέρω έρευνας, λόγω της απλότητας της. Ο Danguy 26 δε βρήκε καμία σχέση συγκρίνοντας τα αποτελέσματα του με τη μέθοδο του ανοσοφθορισμού και τη βιοχημική μέθοδο.…”
Section: γ ζυζητησηunclassified